Size-fractionated primary production in the open Southern Ocean in austral spring - Jochem, Frank F.J.; Mathot, Sylvie; Quéguiner, Bernard (1995)
Size-fractionated primary production was measured by carbon-14 uptake incubations on three transects between 47°S and 59°30′S along 6°W in October/November 1992. Open Antarctic Circumpolar Current and ice-covered Weddell Gyre water showed comparable low productivity (∼0.3 gCm-2 day-1) and size distribution. Picoplankton (<2 μm) was the dominant size fraction, contributing approximately half to the total water column production. The significance of larger (>20 μm) phytoplankton was only minor. Productivity in the Polar Front Zone north of 50°S, with higher water column stability, was up to 10 times higher with microplankton (>20 μm) being predominant. No ice-edge bloom occurred over the 2 months study period; this is explained by non-favourable hydrographic conditions for blooming and the lack of melt-water lenses upon ice retreat. Picoplankton tended to make higher contributions at lower water column stability, and microplankton to make higher contributions at higher stability. Mixing, together with light climate, are discussed as the driving forces for Antarctic primary production and for its size structure. © 1995 Springer-Verlag. SCOPUS: ar.j info:eu-repo/semantics/published